Positive Impact Of Health Education Through Video Media to the Improvevement of Adolescent Reproductive Health Knowledge - Gufron Wahyudi; Rahmawati Raharjo (Journal of Ners and Midwifery, 2023)
Reproductive health knowledge is a critical aspect of adolescents' overall well-being, and its effective promotion plays a pivotal role in ensuring their long-term health and decision-making. In recent years, the utilization of video-based health education has gained popularity as a means of delivering information to this demographic. However, it was imperative to investigate the extent to which this innovative approach truly influences adolescents' knowledge. This study employed a quasi-experimental two-group pretest-posttest design and involved a total of 34 respondents who were selected through a comprehensive total sampling technique. The primary objective was to evaluate the impact of video-based health education on adolescents' knowledge of reproductive health. Statistical analysis was conducted using the Mann-Whitney Test and the Wilcoxon Test, revealing a statistically significant improvement in reproductive health knowledge among the participants, as indicated by a p-value of 0.000, which was less than the significance level of 0.05. These findings emphasized the effectiveness of video-based health education as a powerful tool in enhancing adolescents' comprehension of reproductive health matters. It underscores the importance of integrating video-based education into comprehensive health promotion strategies targeted at adolescents, as it has the potential to significantly contribute to their overall health awareness and decision-making capabilities.